2017
DOI: 10.1557/jmr.2017.290
|View full text |Cite
|
Sign up to set email alerts
|

Nanoenabling electrochemical sensors for life sciences applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 158 publications
1
3
0
Order By: Relevance
“…The sponge-like 3D structure with interconnecting pores of 20-30 nm and ligaments of 30-50 nm that typifies NPG is shown in Figure 3d. In the presence of 1 mM FCA, the measured CVs at 10 mV s −1 displayed sigmoidal responses reaching a steady-state current, typical of a single electron oxidation occurring at a micron-scale electrode and consistent with comparable array types previously reported [67]. This confirmed that the performance of the on-chip three-electrode cell was not compromised by the reduced cell volume (~200 µL when using the on-chip pseudoreference electrode), the on-chip counter electrode dimensions or by electrical contact using spring-loaded probes.…”
Section: Npg Modification Of Microdisc Arrays With High Reproducibilitysupporting
confidence: 89%
See 2 more Smart Citations
“…The sponge-like 3D structure with interconnecting pores of 20-30 nm and ligaments of 30-50 nm that typifies NPG is shown in Figure 3d. In the presence of 1 mM FCA, the measured CVs at 10 mV s −1 displayed sigmoidal responses reaching a steady-state current, typical of a single electron oxidation occurring at a micron-scale electrode and consistent with comparable array types previously reported [67]. This confirmed that the performance of the on-chip three-electrode cell was not compromised by the reduced cell volume (~200 µL when using the on-chip pseudoreference electrode), the on-chip counter electrode dimensions or by electrical contact using spring-loaded probes.…”
Section: Npg Modification Of Microdisc Arrays With High Reproducibilitysupporting
confidence: 89%
“…As described in the experimental section, NPG modification experiments were performed at gold microdisc array working electrodes by electrodeposition at −1.19 V vs. SCE for 3 s in a solution of 100 mM KAg(CN) 2 and 20 mM KAu(CN) 2 in 250 mM Na 2 CO 3 at pH 13 to yield Au 0.18 Ag 0.82 , followed by etching of the silver component in 25% nitric acid for 2 min and was based on a process described earlier for modification of arrays of gold microbands and gold microdiscs [66,67]. CVs in 1 M NaOH over the range −0.90 to 0.90 V at 10 mVs −1 were recorded vs. SCE in between each step, as shown in Figure 3a.…”
Section: Npg Modification Of Microdisc Arrays With High Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-and nano electrodes become very useful when a high parallelism of analysis is needed and when a low sample volume is required. While aspects regarded to nanoelectrodes physical properties, fabrication and advancements in analytical instrumentation have been reviewed elsewhere [28][29][30], many efforts are oriented to enhance electrode signal using novel redox molecules or improving experimental procedures.…”
Section: Nano-and Microelectrodesmentioning
confidence: 99%